Contribution of individual rivers to Great Barrier Reef nitrogen exposure with implications for management prioritization. (August 2018) - Wolff, Nicholas H.; da Silva, Eduardo Teixeira; Devlin, Michelle; Anthony, Kenneth R.N.; Lewis, Stephen; Tonin, Hemerson; Brinkman, Richard; Mumby, Peter J.
Abstract: Dissolved inorganic nitrogen (DIN) runoff from Great Barrier Reef (GBR) catchments is a threat to coral reef health. Several initiatives address this threat, including the Australian Government's Reef 2050 Plan. However, environmental decision makers face an unsolved prioritization challenge: determining the exposure of reefs to DIN from individual rivers. Here, we use virtual river tracers embedded within a GBR-wide hydrodynamic model to resolve the spatial and temporal dynamics of 16 individual river plumes during three wet seasons (2011−2013). We then used in-situ DIN observations to calibrate tracer values, allowing us to estimate the contribution of each river to reef-scale DIN exposure during each season. Results indicate that the Burdekin, Fitzroy, Tully and Daintree rivers pose the greatest DIN exposure risk to coral reefs during the three seasons examined. Results were used to demonstrate a decision support framework that combines reef exposure risk with river dominance (threat diversity). Highlights: 6792 km 2 of reef habitat and 1234 reefs were exposed to river plumes during the 2011 wet season. Cumulative reef exposure (reef km 2 days) during 2011 was 4 times higher than during 2012 and 2013. A 50% reduction in river DIN loads resulted in up to 77% reduction in exposure to high DIN (>1.0 μM). The Burdekin, Tully, Fitzroy and Daintree contributed the most to reef exposure to riverine DIN. A decision support framework is shown to assist managers prioritize pollution abatement.